2016
DOI: 10.1016/j.jmaa.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium states of the Charney-DeVore quasi-geostrophic equation in mid-latitude atmosphere

Abstract: Abstract. On the predictability of atmospheric blocking in the mid-latitude atmosphere, a quasi-geostrophic beta-plane channel model equation was introduced in a pioneering work by Charney and DeVore in 1979 based on the understanding of quasi-stationary weather patterns. The equation is driven by a zonal thermal flow representing a mid-latitude westerly jet and a wave function representing an ocean land topography. They truncated the equation into a three spectral mode model, which gives rise to the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…For example, many previous studies [3,4,27] demonstrated the existence of multiple equilibrium states of QG flows in the presence of an external topographic forcing and dissipation. Likewise, other studies by [7] showed that nonlinear interaction between waves and mean flows could lead to quasi-stationary flow regions, blocked flows, or zonal flow patterns similar to what observed for Northern Hemisphere midlatitude circulations.…”
supporting
confidence: 57%
“…For example, many previous studies [3,4,27] demonstrated the existence of multiple equilibrium states of QG flows in the presence of an external topographic forcing and dissipation. Likewise, other studies by [7] showed that nonlinear interaction between waves and mean flows could lead to quasi-stationary flow regions, blocked flows, or zonal flow patterns similar to what observed for Northern Hemisphere midlatitude circulations.…”
supporting
confidence: 57%
“…When the concepts of "intransitivity" and "almost intransitivity" were initially introduced to explore the potential longevity of different climate regimes, if they exist, investigating regime changes on weather or short-term climate scales may also be valuable. For instance, Charney and DeVore (1979) [83] proposed that the presence of multiple, stable steady-state solutions in a low-order QG system could lead to the emergence of atmospheric blocking in the form of a stable steady-state solution (e.g., Chen and Xiong 2016 [84]). This phenomenon arises from the interplay of nonlinearity and mechanical and thermal forcing.…”
Section: The Lorenz (1986) Modelmentioning
confidence: 99%
“…Websites such as Kaggle plays a great role in promoting the semantic segmentation of images in practical applications and they are good at semantic editing or based on a more realistic scenario, such as MIT and satellite images, etc, for semantic segmentation in the context of deep learning. There are also a large number of valuable research results, which a large number of researchers have done semantic segmentation and realistic applications based on deep learning. Besides, the deep learning techniques have been applied to various fields of image processing such as other works, making a great breakthrough in traditional image processing.…”
Section: Introductionmentioning
confidence: 99%